The Comparison of Hungarian and Indonesian Curriculum: A Case Study of ISCED 2 Mathematics and Sciences Curriculum - Amalina, I. K.; Suherman, S.; Vidákovich, T.; Puspita, L.; Supriadi, N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
In the twenty-first century, there has been significant and rapid advancement in mathematics and science education. Comparing the educational systems of different countries according to international standards can provide valuable insights for improving educational quality. This study aims to investigate and compare the science and mathematics education systems of two countries, Indonesia and Hungary, specifically at the ISCED 2 level. The Indonesian curriculum used in this study is the most recent version of Curriculum 2013, updated in 2016, while the Hungarian curriculum used is the National Core Curriculum 2020 (NCC). This research is categorized as library research and applies the qualitative descriptive-analytical method. We searched several legal documents of curriculums from both countries in libraries, legal websites, formal institutions, and the archives of the ministries of education. After finding the relevant documents, the authors from each country translated, analyzed, and reviewed them thoroughly. According to the findings, several differences between the two educational systems might generate drawbacks. In Hungary, both science and mathematics curricula are empirical-based and involve activities, whereas in Indonesia, they start from new activities and are content-based. There are also several disjoint topics in mathematics between both countries, such as absolute value and quadratic equations. In Indonesia, science education is focused on biology topics as the main proportion of knowledge and is theoretical-oriented, while in Hungary, it is more varied in topics and is realistic and empirical-oriented. The Hungarian science curriculum is also emphasized on inquiry and experimental activities. To further investigate and compare the education systems, more studies are needed at every level of education.